2013
DOI: 10.1108/rjta-17-01-2013-b006
|View full text |Cite
|
Sign up to set email alerts
|

Apparel Sustainability from a Local Perspective

Abstract: This research takes a bottoms-up approach to sustainable practices of designers within one industry in a specific locale. In researching sustainability in the apparel industry, one must consider the fashion system in which apparel designers operate. This research examines apparel designers in Minnesota and their perspectives about best practices that will encourage sustainability. Designers from a variety of small to large size businesses are interviewed and the results are analyzed to identify present and fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Size of organization too, influences design and sustainability. Mid-market fashion companies are less likely to have well-defined long-term sustainable aims than large mass market retailers (Cooper et al 2013), while the smaller organizational structure of SMEs provides the designer with the potential to strategically influence the whole product lifecycle (Delong et al 2013;Lawless and Medvedev, 2016).…”
Section: Theorymentioning
confidence: 99%
“…Size of organization too, influences design and sustainability. Mid-market fashion companies are less likely to have well-defined long-term sustainable aims than large mass market retailers (Cooper et al 2013), while the smaller organizational structure of SMEs provides the designer with the potential to strategically influence the whole product lifecycle (Delong et al 2013;Lawless and Medvedev, 2016).…”
Section: Theorymentioning
confidence: 99%
“…The research findings support conclusions drawn by Lawless & Medvedev (2016) that current economic models do not support the development and adoption of sustainable fashion practices. This research also provides further evidence of the enormous financial potential and opportunities for MSEs to drive sustainability (Battaglia et al, 2014;DeLong et al, 2016;Lawless & Medvedev, 2016) despite the identified barriers. It was evident that the flexibility, creativity and commitment to the beliefs exhibited by the design entrepreneurs are instrumental in navigating the many challenges that come with running a sustainable fashion business.…”
Section: Discussionmentioning
confidence: 77%
“…Despite the recent emergence of sustainability-orientated innovations and strategies in fashion, little is known about the relevance and application of such strategies for micro-to small-sized enterprises (MSEs). MSEs in the fashion industry have recently been identified as drivers for sustainability as they have more opportunity to connect to the whole product lifecycle (DeLong, Goncu-Berk, Bye, & Wu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence to determine if sustainability is a concern or a motivating factor. DeLong et al (2013) found that the definition of sustainability varied greatly among designers and could be inferred to be part of their daily best practices, even though they did not identify their actions as sustainable. Researchers need to look more deeply at the relationship between stainability and the motivation for domestic manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a strong need to connect globally, local systems can complement and influence the larger industry. Value is added by slowing down the process and designing products that represent the place and local culture, using local resources (DeLong et al , 2013). Berchicci and Bodewes (2005) suggest that for a sustainable product to be successful, the consumer’s environmental concerns must be deeply rooted in the product design.…”
Section: Literature Reviewmentioning
confidence: 99%